EXTH-69. FUNCTIONAL GENOMICS UNCOVER GENETIC DEPENDENCIES IN ATRTS. (12th November 2021) - Merk, Daniel; Hirsch, Sophie; Tsiami, Foteini; Walter, Bianca; Haeusser, Lara; Babaei, Sepideh; Admard, Jakob; Casadei, Nicolas; Roggia, Cristiana; Spohn, Michael; Schittenhelm, Jens; Singer, Stephan; et al.
Abstract: Brain tumors are the leading cause of cancer-related deaths in children. Embryonal brain tumors including medulloblastoma and atypical teratoid rhabdoid tumors (ATRTs) account for 15% of all primary brain and CNS tumors under the age of 14 years, with ATRTs being most prevalent in infants. Despite intensive research efforts, survival estimates for ATRT patients stay relatively low as compared to other tumor entities with a median survival of around 17 months. We here describe genome-wide CRISPR/Cas9 knockout screens in combination with small-molecule drug assays to identify targetable vulnerabilities in ATRTs. Based on functional genomic screening revealing ATRT context-specific genetic vulnerabilities (n = 671 genes), we successfully generated a small-molecule library that shows preferential activity in ATRT cells as compared to a broad selection of other human cancer cell lines. Of note, none of these drugs differentially affect ATRT cells from distinct molecular subgroups, suggesting that top candidate inhibitors might serve as pan-ATRT therapeutic avenues. CDK4/6 inhibitors, among the most potent drugs in our library, are capable of inhibiting tumor growth due to mutual exclusive dependency of ATRTs on either CDK4 or CDK6 . Our approach might serve as a blueprint for fostering the identification of functionally-instructed therapeutic strategies in other incurable diseases beyond ATRT, whose genomic profiles also lack actionable alterations so far.